Blind faith : our misplaced trust in the stock market--and smarter, safer ways to invest - Winslow, Edward, 1954- (BK life book., 2003)
The risk of investing in the stock market has increased remarkably over the last decade. In this period we've seen tremendous volatility in stock prices, a market bubble and its subsequent pop, a parade of corporate scandals, the demise of a leading accounting firm and proven deception by many so-called investment analysts employed by major brokerage firms. In addition, the realities of ever-increasing geopolitical risks contribute to an uncertain economic future. Blind Faith offers a cleverly simple yet revolutionary approach for managing investments in this perpetual high-risk environment. Corporate America and the investment industry have little to gain and lots to lose when investors decide to stop playing the traditional game that can -and has - destroyed trillions of dollars of individual wealth overnight. Readers will be equipped with both the strategy and the tools for success in virtually any economic environment while ending their participation in a system that has taken full advantage of their blind faith and misplaced trust.